Racism in the film The Little Mermaid: Assessing its impact on social media - Jayanti , Elvira Eka; Indriani , Nova; Febrianti, Vera; Purnama , An’nisa; Afifulloh, M (Smart Edu Center, 2024)
The controversy surrounding the casting of Halle Bailey, a black actress, as Ariel in the live-action adaptation of